Characteristic of non-adiabatic tapered fiber towards humidity - Jali, Mohd Hafiz; Abdul Rahim, Hazli Rafis; Md Johari, Md Ashadi; Mohd Yusof, Haziezol Helmi; Ahmad, Aminah; Baharom, Mohamad Faizal; Thokchom, Siddharth; Harun, Sulaiman Wadi (Wydawnictwo SIGMA-NOT, 2021)
This paper reported the characterization of non-adiabatic tapered fiber using flame brushing technique towards humidity. The tapered fibers were exposed to relative humidity concentrations level ranging from 35%RH to 85%RH to observe the optical characteristic. There are several criterions considered for this study such as scattering coefficient (αmf), transmission loss (TL), output light intensity and enhancement factor (ɣ). The relationship between the waist diameter and the other criterions towards the %RH level has been successfully investigated.